Analisis pengaruh Profitabilitas, Struktur Modal dan Total Asset Turnover Terhadap Nilai Perusahaan pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021 - Septiana Kristina Ningrum, Maria; Susanto, Daniel (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to examine the factors that influence the company value of LQ45 companies listed on the Indonesia Stock Exchange (BEI) seen from the annual reports and financial reports of LQ45 companies in the 2017-2021 period. The factors used to see their influence on Company Value are Profitability, Capital Structure, and Total Asset Turn Over. The results of this research show that the Return On Equity and Debt to Equity Ratio variables have an influence on company value. This can be seen in the test results (t), Return On Equity has a significant positive influence with a calculated t of 2,264 > t table of 2.0391 with a significant value of 0.021<0.050, and Debt to Equity Ratio has a significant negative influence with a calculated t of -3,649 > t-table of -2.03915 with a significance of 0.001 < 0.050 so that H1 and H2 are accepted. Meanwhile Total Asset Turn Over has no effect on company value. These results can be seen from the test results (t) with a t-count of -199 < -2.03951 with a significant value of 0.843 > 0.050 so that H3 is rejected. Apart from that, based on the (F) test, Profitability, Capital Structure and Total Asset Turn Over on Company Value have an effect simultaneously (together), this is shown by the calculated F value of 5,324 > F-table of 2.69 and a significant value of 0.004 < 0.050.